(untitled) (Conference Zone, 2022)
This article describes the number of grains per 1 plant in the light gray soils of Kashkadarya region, which is 3.5 to 10.6 times higher than in the late sowing period. At this point, the analysis of the planting scheme revealed that the 90x20-1 scheme is higher than the 90x10- 1 scheme. When the effect of mineral fertilizers on the number of grains in 1 plant was studied, it was stated that the 90x10-1 scheme was high in the early and late period in the 90x20-1 scheme, respectively, early and late.